2018
DOI: 10.1115/1.4040754
|View full text |Cite
|
Sign up to set email alerts
|

Well Placement Optimization With Cat Swarm Optimization Algorithm Under Oilfield Development Constraints

Abstract: Proper well placement can improve the oil recovery and economic benefits during oilfield development. Due to the nonlinear and complex properties of well placement optimization, an effective optimization algorithm is required. In this paper, cat swarm optimization (CSO) algorithm is applied to optimize well placement for maximum net present value (NPV). CSO algorithm, a heuristic algorithm that mimics the behavior of a swarm of cats, has characteristics of flexibility, fast convergence, and high robustness. Oi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…[102] Applied Cauchy mutated CSO to make linear aperiodic arrays, where the goal was to reduce sidelobe level and control the null positions e proposed system outperformed both CSO and PSO [103] Applied CSO and analytical formula-based objective function to optimize well placements CSO outperformed DE algorithm [104] Applied CSO to optimize well placements considering oilfield constraints during development. CSO outperformed GA and DE algorithms [105] CSO applied to optimize the network structure and learning parameters of an ANN model, which is used to predict an ASP flooding oil recovery index e system successfully forecast the ASP flooding oil recovery index [42] Applied CSO to build an identification model to detect early cracks in beam type structures CSO yields a desirable accuracy in detecting early cracks [106] Computational Intelligence and Neuroscience wavelet entropy, ANN, and CSO algorithm to develop an alcohol use disorder (AUD) identification system [64]. Kumar et al combined the CSO algorithm with functional link artificial neural network (FLANN) to remove the unwanted Gaussian noises from CT images [45].…”
Section: Computer Visionmentioning
confidence: 98%
See 1 more Smart Citation
“…[102] Applied Cauchy mutated CSO to make linear aperiodic arrays, where the goal was to reduce sidelobe level and control the null positions e proposed system outperformed both CSO and PSO [103] Applied CSO and analytical formula-based objective function to optimize well placements CSO outperformed DE algorithm [104] Applied CSO to optimize well placements considering oilfield constraints during development. CSO outperformed GA and DE algorithms [105] CSO applied to optimize the network structure and learning parameters of an ANN model, which is used to predict an ASP flooding oil recovery index e system successfully forecast the ASP flooding oil recovery index [42] Applied CSO to build an identification model to detect early cracks in beam type structures CSO yields a desirable accuracy in detecting early cracks [106] Computational Intelligence and Neuroscience wavelet entropy, ANN, and CSO algorithm to develop an alcohol use disorder (AUD) identification system [64]. Kumar et al combined the CSO algorithm with functional link artificial neural network (FLANN) to remove the unwanted Gaussian noises from CT images [45].…”
Section: Computer Visionmentioning
confidence: 98%
“…CSO algorithm has also been applied in the petroleum engineering field. For example, it was used as a good placement optimization approach by Chen et al in [104,105]. Furthermore, Wang et al used CSO algorithm as an ASP flooding oil recovery index forecasting approach [43].…”
Section: Petroleummentioning
confidence: 99%
“…CSO outperformed GA and DE algorithms [107] CSO applied to optimize the network structure and learning parameters of an ANN model, which is used to predict an ASP flooding oil recovery index…”
Section: Computer Vision: Facial Emotionmentioning
confidence: 99%
“…Pappula et al also used Cauchy mutated CSO to make linear aperiodic arrays, where the goal was to reduce sidelobe level and control the null positions[105].5.6 Petroleum Engineering: CSO algorithm has also been applied in the petroleum engineering field. For example, it was used as a good placement optimization approach by Chen et al in[106,107]. Furthermore, Wang et al used the CSO algorithm as an ASP flooding oil recovery index forecasting approach[44].…”
mentioning
confidence: 99%
“…In 2019, Hongwei Chen and et al used three algorithms, CSO (Cat Swarm Optimization), GA, and DE (Differential Evolution), in a simulated model to optimize the placement of oil wells. After conducting simulations, the results showed that the CSO algorithm outperformed GA and DE, effectively addressing the well placement optimization challenge [31]. In 2019, Yazdanpanah, and et al utilized optimization algorithms, including GA, PSO, and HGAPSO (Hybrid GA-PSO), to optimize the placement of oil wells.…”
Section: Introductionmentioning
confidence: 99%